2016
DOI: 10.1523/jneurosci.4499-15.2016
|View full text |Cite
|
Sign up to set email alerts
|

Parsing the Behavioral and Brain Mechanisms of Third-Party Punishment

Abstract: The evolved capacity for third-party punishment is considered crucial to the emergence and maintenance of elaborate human social organization and is central to the modern provision of fairness and justice within society. Although it is well established that the mental state of the offender and the severity of the harm he caused are the two primary predictors of punishment decisions, the precise cognitive and brain mechanisms by which these distinct components are evaluated and integrated into a punishment deci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
44
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 57 publications
(37 reference statements)
3
44
1
Order By: Relevance
“…Thus, to the extent that ball tosses are dictated by the behavioral task, these neural processes may not speak directly to self-agency. Furthermore, self-agency may play a role in decision making more broadly in and beyond social interactions; e.g., in determining individual differences in control-averse behavior (Rudorf et al, 2018), in modulating choice behavior when unexpected outcomes arise from errors in action (Parvin, McDougle, Taylor, & Ivry, 2018), and in mentalizing to assign third-party punishment (Ginther et al, 2016). The current findings may add to this literature and facilitate research of the influences of social exclusion on many other decision making processes that involve social interactions.…”
Section: A Broader Role Of Self-agencymentioning
confidence: 67%
“…Thus, to the extent that ball tosses are dictated by the behavioral task, these neural processes may not speak directly to self-agency. Furthermore, self-agency may play a role in decision making more broadly in and beyond social interactions; e.g., in determining individual differences in control-averse behavior (Rudorf et al, 2018), in modulating choice behavior when unexpected outcomes arise from errors in action (Parvin, McDougle, Taylor, & Ivry, 2018), and in mentalizing to assign third-party punishment (Ginther et al, 2016). The current findings may add to this literature and facilitate research of the influences of social exclusion on many other decision making processes that involve social interactions.…”
Section: A Broader Role Of Self-agencymentioning
confidence: 67%
“…When it comes to evaluating third-party harmful behavior like this, past work has shown that people rely not only on the assessment of the mental state of the perpetrator, but also on the presence of a harmful consequence for the victim (Buon, Seara-Cardoso, & Viding, 2016;Cushman, 2015;Ginther et al, 2016;Young & Tsoi, 2013). In other words, after witnessing harmful event, third-party moral judge reasons about the intentions of the actors ("What was Blythe thinking when he threw his fan off the stage?!")…”
Section: Intention and Outcome In Moral Judgmentmentioning
confidence: 99%
“…For example, the encoding of mental states occurs very early during information processing in the right TPJ7, left TPJ8, and amygdala9. The rTPJ, dmPFC, and PCC are also involved in integrating belief states1011 with other morally relevant pieces of information (e.g., consequences) to construct final moral judgments12131415. On the other hand, the dmPFC is involved in encoding the valence (harmful or neutral) of the beliefs10.…”
mentioning
confidence: 99%